Edukasi terstruktur meningkatkan kompetensi perawat intensive care unit dalam penggunaan papan komunikasi pasien ventilator sadar: A scoping review - Rahayu, Christiana Cesilia Sri Budi; Sindi, Sindi; Eka, Ni Gusti Ayu (Holistik Jurnal Kesehatan, 2026)
Background: Conscious patients receiving mechanical ventilation in the Intensive Care Unit (ICU) often experience communication barriers due to the inability to speak despite preserved cognitive function. This condition contributes to anxiety, frustration, and potentially compromises patient safety and the quality of nursing care. Augmentative and Alternative Communication (AAC), specifically low-tech communication boards, has been recommended as a solution to support communication in conscious patients on ventilators. However, the implementation of AAC in the ICU remains suboptimal due to limited nurse competency and the lack of a standardized and structured educational model. Purpose: To identify the types of AAC communication boards used in conscious patients on ventilators in the ICU and the learning methods reported to be most effective in improving nurse competency in their use. Method: This scoping review was conducted using the Joanna Briggs Institute (JBI) methodology and reported following PRISMA-ScR guidelines. A literature search was conducted in PubMed, CINAHL, and ScienceDirect for publications from 2015–2025. Quantitative, qualitative, and mixed-methods studies were included. Article selection was conducted independently by two reviewers, and methodological quality was assessed using the JBI critical appraisal checklist. Results: Six articles met the inclusion criteria, demonstrating that structured education on the use of AAC communication boards contributed to improved nurses' knowledge, skills, attitudes, and acceptance in facilitating communication with conscious patients on ventilators. Key contributing factors included clinical practice-based training, organizational support, and nurse involvement in intervention development. Identified barriers included time constraints, high nurse workload, and diverse patient clinical conditions. Conclusion: A low-tech AAC communication board is a feasible and practical intervention to support communication in conscious patients on mechanical ventilators in the ICU. Sustainable implementation is strongly influenced by structured nurse education, experiential learning, and institutional support.   Keywords: Communication Board; Conscious Patients on Ventilators; Intensive Care Unit; Nurse Competence; Structured Education.   Pendahuluan: Pasien sadar yang menggunakan ventilasi mekanik di Intensive Care Unit (ICU) sering mengalami hambatan komunikasi akibat ketidakmampuan berbicara meskipun fungsi kognitif tetap terjaga. Kondisi ini berkontribusi terhadap kecemasan, frustrasi, dan berpotensi menurunkan keselamatan pasien serta mutu asuhan keperawatan. Augmentative and Alternative Communication (AAC), khususnya papan komunikasi berteknologi rendah, telah direkomendasikan sebagai solusi untuk mendukung komunikasi pasien ventilator sadar. Namun, implementasi AAC di ICU masih belum optimal akibat keterbatasan kompetensi perawat dan belum tersedianya model edukasi terstruktur yang terstandar. Tujuan: Untuk mengidentifikasi jenis papan komunikasi AAC yang digunakan pada pasien ventilator mekanik sadar di ICU serta metode pembelajaran yang dilaporkan lebih efektif dalam meningkatkan kompetensi perawat dalam penggunaanya. Metode: Penelitian scoping review dengan pendekatan berdasarkan metodologi Joanna Briggs Institute (JBI) dan dilaporkan mengikuti pedoman PRISMA-ScR. Penelusuran literatur dilakukan pada PubMed, CINAHL, dan ScienceDirect untuk publikasi tahun 2015–2025. Studi kuantitatif, kualitatif, dan metode campuran disertakan. Proses seleksi artikel dilakukan secara independen oleh dua penelaah dan kualitas metodologis dinilai menggunakan JBI critical appraisal checklist. Hasil: Sebanyak 6 artikel memenuhi kriteria inklusi, menunjukkan bahwa edukasi terstruktur penggunaan papan komunikasi AAC berkontribusi terhadap peningkatan pengetahuan, keterampilan, sikap, dan penerimaan perawat dalam memfasilitasi komunikasi pasien ventilator sadar. Faktor pendukung utama meliputi pelatihan berbasis praktik klinis, dukungan organisasi, dan keterlibatan perawat dalam pengembangan intervensi. Hambatan yang ditemukan mencakup keterbatasan waktu, beban kerja perawat yang  tinggi, dan variasi kondisi klinis pasien. Simpulan: Papan komunikasi AAC berteknologi rendah merupakan intervensi yang layak dan praktis untuk mendukung komunikasi pasien ventilator mekanik sadar di ICU. Implementasi berkelanjutan sangat dipengaruhi oleh pendidikan perawat yang terstruktur, pembelajaran berbasis pengalaman, dan dukungan institusional.   Kata Kunci: Edukasi Terstruktur; Intensive Care Unit; Kompetensi Perawat; Papan Komunikasi; Pasien Ventilator Sadar.